2018
DOI: 10.1007/s11250-018-1678-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance and ingestive behavior of steers on integrated system using legume and/or energy supplementation

Abstract: This study aimed to evaluate the effect of a mixture of temperate and legume grasses with or without energy supplementation on the performance and feeding behavior of finishing beef steers. Eighteen Nellore-Zebu steers, average 23 months old and body weight (BW) of 380 kg, were used in a continuous grazing system, in a randomized block experimental design. Treatments were ORS: oat (Avena strigosa Schreb) + annual ryegrass (Lolium multiflorum Lam) + supplementation with corn bran; ORVS: oat + ryegrass + vetch (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…According to Barcellos et al (2008), there is a lower animal preference for legumes in tropical regions than grasses and, consequently, a trend for choosing grasses. Similar results (Lazzarotto et al, 2019;Lisbinski et al, 2019) were found in other studies, and the authors verified similar gains between animals on oat + ryegrass pastures mixed with vetch and those that only grazed grasses.…”
Section: Discussionsupporting
confidence: 89%
“…According to Barcellos et al (2008), there is a lower animal preference for legumes in tropical regions than grasses and, consequently, a trend for choosing grasses. Similar results (Lazzarotto et al, 2019;Lisbinski et al, 2019) were found in other studies, and the authors verified similar gains between animals on oat + ryegrass pastures mixed with vetch and those that only grazed grasses.…”
Section: Discussionsupporting
confidence: 89%
“…Supplementation can decrease forage intake due to substitution, wherein higher levels of supplement favor substitution of pasture intake for supplements that increase stocking rate (KLEIN et al, 2015). Additionally, when supplement consumption substitutes part of forage intake, it improves diet quality due to higher energy levels, which allows higher bovine selectivity during grazing (LISBINSKI et al, 2018). The lower SC with an increase of the supplement amount can be associated with greater response of SR to higher levels than the individual gain of the heifers, which is characteristic of the supplement substitution effect.…”
Section: Resultsmentioning
confidence: 99%
“…Mixture between grasses and temperate legumes has proved to be important for feeding beef cattle because these species possess excellent forage quality and provide high yields per area, allowing for long grazing periods, and improving the performance of animals during the critical production period (LISBINSKI et al, 2019). This increase in production is because of the long and later cycle of legume as compared to oat (WAGHORN & CLARK, 2004).…”
Section: Introductionmentioning
confidence: 99%